A phase 2 study of spartalizumab (PDR001) among patients with recurrent or metastatic esophageal squamous cell carcinoma (KCSG HN18-17, K-MASTER project 12) - Dong Ki Lee; Sook Ryun Park; Yeul Hong Kim; Yun-Gyoo Lee; Su-Jin Shin; Beung-Chul Ahn; Sung Sook Lee; Sun Min Lim; Hye Ryun Kim; Byoung Chul Cho; Min Hee Hong (OncoImmunology)
Spartalizumab (PDR001) is a humanized IgG4 monoclonal antibody targeting programmed cell death protein 1 (PD-1). We conducted a single-arm, phase 2 trial to investigate the efficacy and safety of spartalizumab in patients with refractory esophageal squamous cell carcinoma (ESCC). Patients with histologically confirmed ESCC who experienced disease progression after platinum-based chemotherapy received 300 mg of intravenous spartalizumab every three weeks until disease progression or occurrence of unacceptable toxicity. The primary endpoint was centrally assessed objective response according to the Response Evaluation Criteria in Solid Tumors, version 1.1. Adverse events were closely monitored throughout the study. From March 2020 through April 2021, 44 patients with ESCC were enrolled. Of the 44 patients, the objective response rate was 20.5% (95% confidence interval: 8.5–32.4). With a median follow-up of 10.9 months, median progression-free survival and overall survival were 3.2 months and 11.2 months, respectively. In addition, the median duration of response was 24.7 months. The most common grade 3 or 4 adverse event was grade 3 dysphagia (eight [18%] patients). Biomarker analyses explored programmed cell death ligand 1 and CD20 as potential predictive markers for PD-1 blockade. Spartalizumab showed promising activity with a manageable safety profile, indicating its potential as a new treatment option for patients with refractory ESCC.Trial registration The trial was registered at ClinicalTrials.gov under the identifier NCT03785496.